Efficiency of technical and tactical activity of team "Metalist" (Kharkiv ) U 15 in games in the 2012–2013 championship of Ukraine - Перевозник [Vladimir Perevoznyk] Володимир Іванович; Паєвський [Vladimir Paevskyy] Володимир Валерійович; Перцухов [Andrey Pertsuhov] Андрій Анатолійович (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Considered the technical and tactical team activity of young players "Metalist" (Kharkiv ) U 15 in the 2012–2013 championship of Ukraine. Registration of technical and tactical actions were performed by the method of expert evaluation. Recorded performance of short medium ball passes forward, back and cross, as well as the long ball, passes, dribbling, shots on goal. Registered are defense actions: duel combat, tackling and intercept ion of the ball. After each gamewe summed up the competitive activities of each player and the team as a whole. Calculated is gaming performance ratio and coefficient of faults. Determined is the quantity and quality of all technical and tactical actions. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>